2014
DOI: 10.3390/polym6072051
|View full text |Cite
|
Sign up to set email alerts
|

FRP-RC Beam in Shear: Mechanical Model and Assessment Procedure for Pseudo-Ductile Behavior

Abstract: This work deals with the development of a mechanics-based shear model for reinforced concrete (RC) elements strengthened in shear with fiber-reinforced polymer (FRP) and a design/assessment procedure capable of predicting the failure sequence of resisting elements: the yielding of existing transverse steel ties and the debonding of FRP sheets/strips, while checking the corresponding compressive stress in concrete. The research aims at the definition of an accurate capacity equation, consistent with the require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In order to understand this historic inability to accurately predict the FRP contribution to shear resistance, it is necessary to consider the way in which this contribution is determined experimentally. As noted by Petrone and Monti (2014), most research efforts have concentrated on accurately determining an FRP contribution, rather than describing a comprehensive mechanical model for retrofit beam behaviour. This has led to an experimental approach that focuses on identifying a distinct component of shear resistance V frp that represents the FRP 'contribution'.…”
Section: Poor Predictability Of Frp 'Contribution'mentioning
confidence: 99%
See 2 more Smart Citations
“…In order to understand this historic inability to accurately predict the FRP contribution to shear resistance, it is necessary to consider the way in which this contribution is determined experimentally. As noted by Petrone and Monti (2014), most research efforts have concentrated on accurately determining an FRP contribution, rather than describing a comprehensive mechanical model for retrofit beam behaviour. This has led to an experimental approach that focuses on identifying a distinct component of shear resistance V frp that represents the FRP 'contribution'.…”
Section: Poor Predictability Of Frp 'Contribution'mentioning
confidence: 99%
“…Despite considerable research effort and widespread use of this strengthening approach in practice, questions about the accuracy (Lima andBarros 2011, Chen andCheng 2019) and appropriateness (Petrone and Monti 2014) of the models underpinning existing guidance have been raised. In particular, the assumption underlying most current guidance -that the concrete, steel and FRP contributions to resistance are independent -is drawn into question by experimental studies (Bousselham et al 2006, Belarbi et al 2012, Mofidi et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…concrete, FRP, stirrups. According to (Monti, 2014), ACI overestimates the shear strength of reinforced concrete strengthened with FRP.…”
Section: Comparison Of Shear Calculations Using Aci and Isis Codes Acmentioning
confidence: 99%
“…This might be due to possible changes in the strut orientation or additional cracking that may change the contribution of the concrete or existing transverse reinforcement to the shear strength. The interaction of the FRP shear reinforcement with the transversal steel or the concrete is only considered in a few number of the existing formulations (Modifi and Chaallal [12], Monti and Liotta [13], Kotynia [14]; Colotti [15]; Ali et al [16]; Petrone and Monti [17]). Bousselham and Chaallal in [8] concluded that the contribution of concrete remains more or less unchanged after the formation of diagonal cracking for small and medium size beams.…”
Section: Introductionmentioning
confidence: 99%